What are the limiting factors in swim performance? - Pyne, D. (2004)
The traditional model of the three energy systems has been the conventional approach to understanding the fitness requirements for competitive swimming over the last 30 years. The so-called three energy systems model holds that each of these systems provides fuel for muscle contraction powering human movement. These systems are the ATP-PC system `muscle phosphagens` for explosive movements, the anaerobic glycolysis `the lactic acid energy system` for sustained high-intensity exercise, and the aerobic glycolysis (carbohydrate) and lipolysis (fat) system for low to moderate intensity endurance exercise. Taken as read, this model suggests that competitive swimming is largely determined by energy supply and utilisation. Australian swimming coaches are taught the basic principles of the three energy systems model as part of their Level 2 Coaching Accreditation. However the results of scientific investigation and the hard-earned experience of swimming coaches suggest this model has its limitations.